Ứng dụng trí tuệ nhân tạo trong tổ chức hoạt động STEAM từ vật liệu tái chế ở trường phổ thông thông qua hệ thống AI4GREEN - Đỗ Bảo Châu, Đỗ Bảo Châu; Trịnh Thị Phương Thảo, Trịnh Thị Phương Thảo; Đỗ Đức Quyết, Đỗ Đức Quyết; Đinh Hà An Na, Đinh Hà An Na (Tạp chí Giáo dục, 2026)
The 2018 General Education Curriculum promotes the expansion of STEAM education to foster students’ creativity, problem-solving ability, and the application of knowledge to real-life contexts. However, STEAM implementation in many K-12 schools, particularly in disadvantaged areas, remains constrained by limited facilities and resources, while recycled materials, although widely available, have not been effectively utilized as hands-on learning materials. In response to this gap, this study proposes and develops AI4Green, an AI-powered platform designed to identify recycled materials and recommend STEAM projects that align with local conditions, while also supporting teachers in designing lesson plans, worksheets, and organizing learning activities. The results indicate that AI4Green enables recycled materials to be leveraged as low-cost learning resources, enhances the feasibility of STEAM implementation under resource-limited conditions, and improves both teacher support and students’ hands-on learning experiences.